INTENSITAS PERGERAKAN TRANSPORTASI DI DKI JAKARTA KEBIJAKAN PSBB DAN PPKM SELAMA MASA PANDEMI COVID-19 - Iskumaila Khoirunnisa; Mega Novetriskha Putri; Darmawan Listya Cahya; Dayu Ariesta Kirana Sari (Jurnal Pensil : Pendidikan Teknik Sipil, 2022)
Currently, the conditions that are happening in Indonesia and even the world are, the outbreak of the Covid-19 virus (Covid-19 Pandemic), which has changed the arrangement in the activity of human social life. Based on the policies imposed, namely PSBB and PPKM by the government, it has an impact on human behavior patterns in daily life, especially in terms of transportation movements. This research will discuss these problems and raise "Analysis of the Intensity of Transportation Movements in DKI Jakarta During the Covid-19 Pandemic Period of 2020-2021". The purpose of this study is to analyze the intensity of transportation movements during the period when the PSBB and PPKM policies were implemented during the Covid-19 pandemic. The method used is quantitative descriptive statistics with correlation analysis techniques followed by normality tests and Kolmogorov Smirnov tests. By using the variables of travel frequency, travel distance, travel time, travel intent, travel location, mode of transportation, and transportation cost fares. In this study, it was shown that there were four variables that experienced changes in several variables between the implementation of the PSBB and PPKM policies, namely weekend frequency, travel time, travel location, and transportation cost rates. There is a decrease in frequency change from very frequent to rare, in the variable distance travel there is a slight increase in mileage, travel time there is a decrease in the range of > 2 hours to 1-2 hours. As for the purpose, location, mode of transportation, and cost fares tend to have small changes.